Bráðaofnæmi hjá 20-44 ára Íslendingum - Davíð Gíslason; Þórarinn Gíslason; Þorsteinn Blöndal; Hrafnkell Helgason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open This is a part of a second stage of EC Respiratory Health Survey and the aim of this study is to estimate the prevalence of atopic allergy among urban population of men and women aged 2CM4 years, living in the capital Reykjavik and suburbs. Altogether 800 individuals were invited of whom 570 participated (77%). All participants answered questionnaire and 540 individuals were skin prick tested by 12 allergens. 20.5% had positive skin tests, defined as at least one allergen positive by a weal reaction of 5=3 mm, 20.1% male and 20.9% female. The highest prevalence of allergy was in the agegroup 20-24 years. Results of single allergens: timothy grass 8.5%, cat 7.6%, dog 6.3%, D. pteronyssinus 6.1%, Lepidoglyphus destructor 3.2%, birch 3.0% and Cladosporium 1.1%. Other allergens reacted positive in less than 1% each; altogether 11.2% were positive to one or more animals and 10.6% to timothy and/or birch. RAST tests were done by five allergens. RAST results =50.35 ku/1 (RAST class 5=1) to timothy was 11.9%, to cat 7.5%, to D pteronyssinus 9.2%, to birch 5.9% and to cladosporium 6.5%. The only statistically significant risk factor for allergy was mothers history of allergy symptoms. Compared to already published data from other EC Respiratory Health Survey countries, the prevalence of atopic allergy appear to below in Iceland. Þessi rannsókn er hluti af öðrum áfanga Evrópukönnunarinnar um lungu og heilsu (The European Community Respiratory Health Survey) og fjallar um tíðni bráðaofnæmis hjá 20-44 ára Íslendingum í þéttbýli. Af 800 einstaklingum sem boðið var til könnunarinnar, tóku 570 þátt í henni með því að svara spurningalistum, 540 voru húðprófaðir með pikk aðferð og hjá 522 voru gerð RAST próf. Húðpróf voru túlkuð sem jákvæð ef húðsvörunin var >3mm. Sá sem hafði eina eða fleiri jákvæðar húðsvaranir var talinn hafa ofnæmi. Tíðni ofnæmis var 20,5%; hjá körlum 20,1% og hjá konum 20,9%. Tíðni ofnæmis var hæst í ...